Cancers of unknown primary: Survival by histologic type, demographic features, and treatment in the U.S. Military Health System. (February 2023) - Bytnar, Julie A.; Lin, Jie; Moncur, Joel T.; Shriver, Craig D.; Zhu, Kangmin
Abstract: Background: Cancers of unknown primary (CUP), a group of heterogenous metastatic cancers lacking a known primary site, have poor prognosis. This study compared survival of CUP by histologic type, patient characteristics, and treatment in the U.S. Military Health System (MHS), which provides universal care to its members. Methods: Patients histologically diagnosed with CUP were identified from the U.S. Department of Defense (DoD)'s Automated Central Tumor Registry. Median survival with 95 % confidence intervals was calculated for demographic and treatment variables by histologic type. A multivariable accelerated failure time model estimated time ratios and 95 % confidence intervals. Results: The study included 3358 CUP patients. The most prevalent CUP in this study was well- and moderately-differentiated adenocarcinomas. Median survival varied by histologic type with squamous cell carcinoma having the longest at 25.1 months and poorly-differentiated carcinomas having the shortest at 3.0 months. For each histologic type, survival was generally similar by sex and active-duty status although women with well- and moderately-differentiated adenocarcinoma had longer survival than their male counterparts. Younger patients tended to have longer survival than those aged 65 years or older. Generally, there were no racial differences in survival except poorer survival for Black patients than White patients in the group of other histologic types. Patients with chemotherapy and radiation treatment generally had improved survival whereas patients with squamous cell carcinoma who received chemotherapy had shorter survival than those without. Conclusion: Survival generally did not differ between racial groups, which may be related to equal healthcare access despite racial background. Further studies are warranted to better understand how survival in the MHS compares with that in the general U.S. population. Highlights: Factors for CUP survival independent of pathologic features are unknown. We studied factors related to CUP death by histology in a universal health system. Survival time was similar by sex and longer in those younger and treated. There were largely no racial differences in survival in this universal access system.